Intra-articular Injection of Kartogenin-Incorporated Thermogel Enhancing Osteoarthritis Treatment - Wang, Shao-Jie; Qin, Ji-Zheng; Zhang, Tong-En; Xia, Chun (Frontiers in Chemistry, 2019)
To provide a vehicle for sustained release of cartilage-protective agent for the potential application of osteoarthritis (OA) treatment, we developed a kartogenin (KGN) -incorporated thermogel for intra-articular injection. We fabricated a poly(lactide-co-glycolide)-block-poly(ethylene glycol)-block-poly(lactide-co-glycolide) (PLGA−PEG−PLGA) thermogel as a KGN carrier for IA injection. OA chondrocytes were cultured in thermogel with or with no KGN to investigate the effect of KGN thermogel on cartilage matrix. The in vivo effect of KGN thermogel on OA was examined in a rabbit OA model. The KGN thermogel showed a sustained in vitro release of KGN for 3 weeks. OA chondrocytes proliferated well both in thermogel and KGN thermogel. In addition, OA chondrocytes produced higher amount of (type 2 collagen (COL-2) and glycosaminoglycan (GAG)), as well as lower level of matrix metalloproteinase 13 (MMP-13) in KGN thermogel that those in thermogel with no addition of KGN. The gene analysis supported that KGN thermogel enhanced expression of hyaline-cartilage specific genes Col 2 and AGC, and inhibited the expression of MMP-13. Compared with intra-articular injection of saline or thermogel containing no KGN, KGN thermogel can enhance cartilage regeneration and inhibit joint inflammation of arthritic knees in a rabbit ACLT-induced OA model at 3 weeks after the injection. Therefore, the KGN-incorporated PLGA−PEG−PLGA thermogel may provide a novel treatment modality for OA treatment with IA injection